Current Status of Lecturer Qualifications and the Need for Improving Qualifications in International-Level Mechanical Engineering – Automation Education in Vietnam - Dương Thị Kim Oanh; Lê Hiếu Giang; Đặng Thị Diệu Hiền (Journal of Technical Education Science, 2025)
Training high-quality human resources for various career fields in the context of international integration and the Fourth Industrial Revolution requires lecturers who meet the requirements of professional qualifications and foreign languages. To train international-level human resources in the field of Mechanical Engineering – Automation, lecturers in Mechanical Engineering, Automation, and other fields related to Mechanical Engineering and Automation need to meet the requirements of professional qualifications and foreign languages. However, there is still a research gap in Vietnam regarding the qualifications of lecturers in the aforementioned fields. This study aims to determine the current status of qualifications and the need to improve the qualifications of lecturers in Mechanical Engineering, Automation, and other fields related to Mechanical Engineering and Automation. This study used a questionnaire survey method to collect data from 134 lecturers, 1184 students from nine public universities training in Mechanical Engineering, Automation, and related majors, and 159 alumni who graduated from the above-mentioned majors in Vietnam. The findings showed that the qualifications of lecturers in Mechanical Engineering, Automation, and related fields surpass the national average. In addition, more than three-quarters of lecturers were evaluated to meet and fully meet the training requirements of Mechanical Engineering – Automation in the context of international integration and Industry 4.0. Lecturers in Mechanical Engineering, Automation, and related fields are in high demand to improve their academic degrees, academic titles, professional titles, knowledge and professional skills, foreign language proficiency, and teaching and scientific research skills.